Host autophagy machinery is diverted to the pathogen interface to mediate focal defense responses against the irish potato famine pathogen - Dagdas, Yasin F. (2018)
During plant cell invasion, the oomycete Phytophthora infestans remains enveloped by host-derived membranes whose functional properties are poorly understood. P. infestans secretes a myriad of effector proteins through these interfaces for plant colonization. Recently we showed that the effector protein PexRD54 reprograms host-selective autophagy by antagonising antimicrobial-autophagy receptor Joka2/NBR1 for ATG8CL binding (Dagdas et al., 2016). Here, we show that during infection, ATG8CL/Joka2 labelled defense-related autophagosomes are diverted toward the perimicrobial host membrane to restrict pathogen growth. PexRD54 also localizes to autophagosomes across the perimicrobial membrane, consistent with the view that the pathogen remodels host-microbe interface by co-opting the host autophagy machinery. Furthermore, we show that the host-pathogen interface is a hotspot for autophagosome biogenesis. Notably, overexpression of the early autophagosome biogenesis protein ATG9 enhances plant immunity. Our results implicate selective autophagy in polarized immune responses of plants and point to more complex functions for autophagy than the widely known degradative roles.